Temperature-insensitive fiber optic deformation sensor embedded in composite material - Domański, Andrzej W; Lesiak, Piotr; Mileńko, Karolina; Boczkowska, Anna; Budaszewski, Daniel; Ertman, Sławomir; Woliński, Tomasz R (Photonics Letters of Poland, 2009)
Composite structures are made of two or more components with significantly different physical or chemical properties and they remain separate and distinct in a macroscopic level within the finished structure. This feature allows for introducing optical fiber sensors into the composite material. These sensors can demonstrate stress distribution inside tested material influenced by external tensions. In the function of the sample bend the biggest deformation is created at the surface. In the middle of the sample strain is almost equal to zero. A fiber optic sensor placed in the center of the composite material is sensitive only to temperature changes, whereas a fiber sensor placed on the surface is sensitive simultaneously to temperature and to deformations. The use of the centre fiber as a temperature compensation component is presented in this paper. Full Text: PDF References: T. R. Wolinski, "Polarimetric Optical Fibers and Sensors", Progress in Optics, ed. Emil Wolf (North Holland, Amsterdam), vol. XL, pp. 1-75 (2000) T. R. Wolinski, "Polarization Phenomena in Optical Systems", in Enc. Opt. Engineering, ed. R. Diggers, M. Dekker, New York, pp. 2150-2175 (2003) W. J. Bock, A. W. Domanski, T. R. Wolinski, "Influence of High Hydrostatic Pressure on Beat Length in Highly Birefringent Single-Mode Bow-Tie Fibers", Appl. Optics, vol. 29, 3484-3488 (1990)[CrossRef] Kuang KSC, Kenny R, Whelan MP, Cantwell WJ, Chalker PR. "Embedded fiber Bragg grating sensors in advanced composite materials", Composite Science and Technology, 61, (2001) 1379-1387[CrossRef] Guemes JA, Diaz-Carrilo Menendes JM. Measurement of strain distribution in bonded joints by fiber Bragg gratings. SPIE 1998; [CrossRef] Guemes JA, Diaz-Carrilo Menendes JM. "Response of Bragg grating fiber-optic sensors when embedded in composite laminates", Composite Science and Technology, 62, (2002) 959-966[CrossRef] Reyes G, Cantwell WJ. The mechanical properties of fiber-metal laminates based on glass fibre reinforced polypropylene. Composites Science and Technology 2000.[CrossRef] Davies P, Cantwell WJ. Fracture of glass/polypropylene laminates: influence of cooling rate after moulding. Composites 1994.[CrossRef] Peters K, Studer M, Botsis J, Iocco A, Limberger HG, Salathe RP. Measurement of stress concentrations using embedded optical fiber Bragg grating sensors. SPIE 1999.[CrossRef] T. K. Gangopadhyay, M. Majumder, A. K. Chakraborty, A. K. Dikshit, D. K. Bhattacharya, "Fibre Bragg grating strain sensor and study of its packaging material for use in critical analysis on steel structure", Sensors and Actuators A, 150, (2009), 78-86[CrossRef] N. C. Eaton, M. J. Curran, J. P. Dakin, H. Geiger, "Fiber Optic Bragg Grating Sensor Measurements in Composite Materials", Smart Composites, 20-24 September 1993, Bordeaux, France